2018
DOI: 10.1096/fj.201801152rr
|View full text |Cite
|
Sign up to set email alerts
|

A novel peripheral cannabinoid 1 receptor antagonist, AJ5012, improves metabolic outcomes and suppresses adipose tissue inflammation in obese mice

Abstract: The overactivity of cannabinoid 1 receptor (CB1R) is associated with obesity and type 2 diabetes. First‐generation CB1R antagonists, such as rimonabant, offered therapeutic advantages for the control of obesity and related metabolic abnormalities, but their therapeutic potential was limited by undesirable neuropsychiatrie side effects. Here, we evaluated AJ5012 as a novel potent peripheral CB1R antagonist and, using this antagonist, investigated the role of peripheral CB1R on adipose tissue inflammation in obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…Recently, significant research has been conducted on peripherally restricted CB1 antagonists or inverse agonists [218]. For instance, AJ5012 (10-20 mg/kg/day), a peripheral CB1 antagonist, was reported to cause a significant weight loss, increase energy expenditure, ameliorate glycemic control and insulin sensitivity, and to reduce inflammation in rodent model [219]. Similarly, AJ5018 (10 mg/kg/day) was shown to improve metabolic abnormalities and suppress adipose tissue inflammation via moderation of macrophage infiltration, activation of the NLRP3 inflammasome, and reducing production of pro-inflammatory cytokines in mice [220].…”
Section: Obesitymentioning
confidence: 99%
“…Recently, significant research has been conducted on peripherally restricted CB1 antagonists or inverse agonists [218]. For instance, AJ5012 (10-20 mg/kg/day), a peripheral CB1 antagonist, was reported to cause a significant weight loss, increase energy expenditure, ameliorate glycemic control and insulin sensitivity, and to reduce inflammation in rodent model [219]. Similarly, AJ5018 (10 mg/kg/day) was shown to improve metabolic abnormalities and suppress adipose tissue inflammation via moderation of macrophage infiltration, activation of the NLRP3 inflammasome, and reducing production of pro-inflammatory cytokines in mice [220].…”
Section: Obesitymentioning
confidence: 99%
“…Those exceed the C max of Rimonabant in the serum of treated mice by two to three orders of magnitude and may be sufficient for initiation of its direct CB1R-dependent and/or independent lipolytic activity. Nevertheless, the direct CB1R-independent lipolytic activity of Rimonabant as detectable in vitro might be of minor importance in vivo since (i) Rimonabant has been shown to exert no significant effects on body weight gain, adipose tissue mass and cellular adiposity in CB1R knockout mice fed a high-fat diet, which are lean and resistant to diet-induced obesity [54], (ii) the transcriptional patterns in white adipose tissue and lipolysis stimulation are similar between Rimonabant-treated obese and high fat diet-fed CB1R knockout mice [55] and (iii) other known direct Rimonabant effects on adipocytes, as manifested in the induction of mRNA and protein expression, as well as in the secretion of adiponectin in cultured mouse 3T3 F442A adipocytes, were recapitulated in the adipose tissue of Rimonabant-treated wild type, but not CB1R knockout mice [28]. Thus, the available animal data favour a CB1R-mediated mechanism for the upregulation of adipocyte lipolysis during acute Rimonabant treatment, such as nervous stimulation in response to antagonism of hypothalamic CB1R, albeit a comparative analysis of serum FA levels between Rimonabant-treated wild type and CB1R knockout mice is still missing.…”
Section: Physiological Relevance Of the Direct Lipolytic Activity Of mentioning
confidence: 99%
“…Addressing the CB1R and/ or LD at adipose tissue, exclusively, has the crucial advantage of bypassing putative psychiatric side effects in course of engagement of hypothalamic CB1R. In fact, a novel potent CB1R antagonist, which has a low brain-to-plasma concentration distribution and does not exhibit centrally mediated neurobehavioral effects, was recently found to trigger significant weight loss and improvement of glycemic control, insulin sensitivity and adipose tissue inflammation in the absence of relevant reduction of food intake [55]. In addition, a different and strictly peripheral CB1R antagonist was demonstrated to increase the expression of genes involved in brown adipose tissue thermogenesis, to decrease the LD size in brown adipocytes and to enhance uncoupled respiration [19].…”
Section: Physiological Relevance Of the Direct Lipolytic Activity Of mentioning
confidence: 99%
“…Tat‐CBR1 reduced the expression of pro‐inflammatory cytokines by suppressing the expression of NF‐κB and mitogen activated protein kinase (MAPK) (Kim et al, 2015). Many studies also demonstrated that CBR1 could reduce inflammation in ocular (Thapa and Cairns 2020), obesity (Han et al, 2019; Grunewald et al, 2019) and rheumatoid arthritis synovial fibroblasts (Fechtner and Ahmeds 2017). Therefore, FFA alleviated the inflammation and oxidative stress partially by up‐regulating the CBR1 expression.…”
Section: Discussionmentioning
confidence: 99%